Fungal pseudoaneurysm in pediatric patients: presentation of two cases - Hernández, Belen Domingo Cruz; Castelan, Paola Gonzalez; Montaño, Norma Guadalupe Bueno; Gudiño, Lynn Nahomy Loera; Velasco, Evelyn Monserrat González; Maya, Gabriela Martínez; Hernandez, Natalia Angelica Pucheta (International Journal of Research in Medical Sciences, 2025)
Pseudoaneurysms are a rare and serious complication of infective endocarditis (IE), especially in patients with previous cardiac surgery. They can lead to serious complications, such as rupture, compression of cardiac structures or fistulization. The incidence is not exact, although it is known that certain congenital heart defects and surgical procedures can increase the risk of developing it. We present the cases of two patients who underwent surgery for the treatment of their congenital heart disease, presenting as a complication the development of infectious pseudoaneurysm: the first is a 2-year-old female patient, with a diagnosis of tetralogy of fallot, who underwent surgical correction at 22 months of age; 4 months after correction, he went to our hospital where a transesophageal echocardiogram showed loss of continuity at the level of the right sinus of Valsalva secondary to a 46×44 mm pseudoaneurysm, which generated obstruction of the outflow tract of the right ventricle, so it was decided to undergo the Bentall bono procedure. The second case is a 12-year-old female patient with a diagnosis of pulmonary atresia with ventricular septal defect (VSD), a rastelli procedure was performed at 12 months, presenting with fever, cough in fits and a pulsatile mass of 6×7 cm in the upper third of the wound wound. A transthoracic echocardiogram was performed, observing loss of continuity at the level of the pulmonary artery secondary to a 60×75 mm pseudoaneurysm, which causes dynamic obstruction at the level of LVST. Complete resection of the pseudoaneurysm capsule was performed, a bovine pericardium patch (Peri-Guard) was placed, and a mediastinal cavity was cleaned, and due to high suspicion of mediastinitis, it was decided to submit to the Molina protocol.